Characteristic Features of REE and Pb–Zn–Ag Mineralizations in the Na Son Deposit, Northeastern Vietnam. Issue 4 (October 2016) - Pham‐Ngoc, Can; Ishiyama, Daizo; Tran, Tuan Anh; Hoshino, Mihoko; Taguchi, Sachihiro
Abstract: The Na Son deposit is a small‐scale Pb–ZnPb–Zn–Ag deposit in northeast Vietnam and consists of biotite–chlorite schist, reddish altered rocks, quartz veins and syenite. The biotite–chlorite schist is intruded by syenite. Reddish altered rocks occur as an alteration halo between the biotite–allanite‐bearing quartz veins and the biotite–chlorite schist. Allanite occurs in the biotite–allanite‐bearing quartz veins and in the proximal reddish altered rocks. Rare earth element (REE) fluorocarbonate minerals occur along fractures or at rim of allanite crystals. The later horizontal aggregates of sulfide veins and veinlets cut the earlier reddish altered rocks. The earlier Pb–Zn veins consist of a large amount of galena and lesser amounts of sphalerite, pyrite and molybdenite. The later Cu veins cutting the Pb–Zn veins include chalcopyrite and lesser amounts of tetrahedrite and pyrite. The occurrences of two‐phase H2 O–CO2 fluid inclusions in quartz from biotite–allanite‐bearing quartz veins and REE‐bearing fluorocarbonate minerals in allanite suggest the presence of CO2 and F in the hydrothermal fluid. The oxygen isotopic ratios of the reddish altered rocks, biotite–chlorite schist, and syenite range from +13.9 to +14.9 ‰, +11.5 to +13.3 ‰, and +10.1 to +11.6 ‰, respectively. Assuming an isotopic equilibrium between quartz (+14.6 to +15.8 ‰) and biotite (+8.6 ‰) in the biotite–allanite‐bearing quartz vein, formation temperature was estimated to be 400°C. At 400°C, δ 18 O values of the hydrothermal fluid in equilibrium with quartz and biotite range from +10.5 to +11.7 ‰. These δ 18 O values are consistent with fluid that is derived from metamorphism. Assuming an isotopic equilibrium between galena (+1.5 to +1.7 ‰) and chalcopyrite (+3.4 ‰), the formation temperature was estimated to be approximately 300°C. The formation temperature of the Na Son deposit decreased with the progress of mineralization. Based on the geological data, occurrence of REE‐bearing minerals and oxygen isotopic ratios, the REE mineralization is thought to result from interaction between biotite–chlorite schist and REE‐, CO2 ‐ and F‐bearing metamorphic fluid at 400°C under a rock‐dominant condition. Abstract : REE and Pb‐Zn‐Ag mineralizations coexist in a small scale Na Son deposit, northeastern Vietnam. The REE mineralization in the Na Son deposit was related to the formation of reddish altered rocks. The reddish altered rocks result from rock‐water interaction between biotite‐chlorite schist and REE‐, CO2‐ and F‐bearing fluid, which was derived from metamorphic fluid, at 400oC and rock‐dominant condition.